Sustainable multifunctional bioactive films incorporated with ultrasound-synergized pH-shift modified rice residue protein for berry preservation - Zhepeng Zhang; Ruiqi Long; Teng Zhao; Limei Yin; Lijin Wang; Ronghai He; Zhiming Guo (Food Packaging and Shelf Life, 2026)

Coupled evolution of marine chemocline and nitrogen cycling on continental margins during the Middle Ordovician cooling - Chaogang Fang; Bolin Zhang; Mu Liu; Min Zeng; Haibo Huang; Chengcheng Zhang; Long Teng; Xiangli Wang; Guang-Yi Wei (Global and Planetary Change, 2026)

Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

A climatic threshold regulating Cenozoic silicate weathering and climate stability - Pan Zhang; Kang-Jun Huang; Yan Hu; Fang-Zhen Teng; Long Ma; Tian-Yi Huang (Earth and Planetary Science Letters, 2026)

Detecting SSC in litchi fruits using NIR-enhanced RGB camera combined with VNIR-ENIR transmittance hyperspectral image reconstruction - Teng Long; Yibin Luo; Junjie Li; Yucheng Ma; Zhi Li; Manyi Guan; Xunjing Chen; Nan Li; Jing Zhao; Yubin Lan; Yongbing Long (Food Chemistry, 2026)

Biofoam-derived konjac glucomannan edible 3D porous scaffolds for enhanced probiotic biofilm formation and freeze-drying tolerance - Qiu Qin Zhang; Shan Qin; Jie Shi; Teng Long Miao; Zhen Jia; Ming Sheng Dong; Hui Wang (Food Hydrocolloids, 2026)

Study on bidirectional fluid-structure interaction characteristics of coolant pipes for reactor coolant pump under steady condition - Teng Niu; Yi Bin Li; Hai Long Yuan; Xue Zhao; Kong Sheng Liu; Ren Hui Zhang (Annals of Nuclear Energy, 2026)

Microbial sulfur metabolism affects methane oxidation efficiency of anaerobic methane oxidation in different medium environments - Xunsen Chen; Peng Huang; Wenwen Huang; Zhenzhen Peng; Shubing Li; Yi Tang; Mengchen Lu; Teng Guo; Fangrong Wei; Jinshao Ye; Huaming Qin; Yan Long (International Biodeterioration & Biodegradation, 2026)

Chromosome-level genome assembly, genome-wide association and developmental transcriptomics converge on lipid and energy metabolism as the regulatory core of wing polyphenism in Bolivaritettix circocephalus - Wei-An Deng; Zheng Li; Cai-Li Teng; De-Long Guan (Insect Biochemistry and Molecular Biology, 2026)

Effect of arsenic-contaminated irrigation water exposeure combined with conventional and biodegradable microplastics on arsenic fractionation in the paddy soil - Haotian Yu; Fan Wu; Feng Peng; Keyu Long; Yihui Wei; Teng Ma (Environmental Pollution, 2026)

Prediction of Arctic sea ice concentration and thickness using a cross-attention enhanced PredRNN - Teng Long; Jinli Xiao; Hailong Cui; Huanhuan Li; Zaili Yang; Yaqing Shu (Ocean Engineering, 2026)

From metabolic reprogramming to diagnostic tool: A machine learning framework identifies biomarkers for soil microplastic stress in rice - Ding Sheng; Yao Liu; Shanshan Yin; Yaowu Cao; Long Teng; Kejie Cai; Hongbing Chen; Jun Cao; Zongqing Ding; Zukai Zhang; Jiong Gao; Chen Yang; et al. (Journal of Hazardous Materials, 2026)

Granite weathering revealed by magnesium isotopes fractionation: Implications for the flux dynamics and global carbon sink - Kai Luo; Jin-Long Ma; Fang-Zhen Teng; Gang-Jian Wei; Guan-Hong Zhu; Jia-Rong Liu; Zhuo-Ying Zhang; Zhi-Bing Wang (Chemical Geology, 2026)

GAS6 Mediates Benzo[a]pyrene-Induced Pathological Cardiac Hypertrophy via the mTOR/HIF-1α Glycolytic Remodeling Axis - Guangming Li; Feihu Long; Zhiyue Liu; Jiarui Nicole Fu; Yuanyin Teng; Shanshan Cai; Xiaoling Zhang; Yingji Wang (Chemico-Biological Interactions, 2026)

Experimental investigation·of damage constitutive model for granite under triaxial compression: Insights from acoustic emission technology and fractal theory - Yang Zhao; Yan-long Li; Lei She; Yuan Yao; Xiao-jing Li; Hao-teng Wang; Xin-jian Sun; Ming-ming He (Engineering Geology, 2026)

Phytic acid–engineered TiO2/cellulose composite hydrogels featuring multidentate phosphate sites for efficient Cu(II)/La(III) adsorption - Shiqi Han; Yan Long; Xiangbo Fan; Fanfan Zhang; Daoguang Teng; Guixia Fan (Carbohydrate Polymers, 2026)

A stochastic reaction-diffusion HIV/AIDS model with implications for long-Acting ART - Baozhou Gao; Yantao Luo; Long Zhang; Zhidong Teng (Mathematical Biosciences, 2026)

The impact of migration-mediated multi-threshold control strategies on disease spread of a Filippov patch epidemic model - Cunjuan Dong; Long Zhang; Zhidong Teng (Mathematical Biosciences, 2026)

Low-temperature selective catalytic reduction of NH3 over VPO composited Mn-based catalysts with superior N2 selectivity: Mechanism of inhibiting N2O formation by experiment and DFT - Jin Jiang; Yixuan Teng; Yong Jia; Mingyan Gu; Lina Guo; Fanyu Meng; Jian Yu; Xilou Ding; Shule Zhang; Hongming Long (Journal of Environmental Chemical Engineering, 2026)

Superoxide dismutase/peroxidase-like MoS2 quantum dots enhance ammonia synthesis by Klebsiella pasteurii - Meng-Xin Zhao; Si-Ru Chen; Shan-Shan Hu; Ting-Ting Liu; Jia-Le Teng; Ya-Wen Yu; Jia-Long Zhang; Xue-Ru Zhou; Qun-Feng Ye; Su-Fang Qin; Le-Xing You (Journal of Environmental Chemical Engineering, 2026)

TRIM37 promotes antibacterial defense by regulating antimicrobial peptides in Chinese mitten crab (Eriocheir sinensis) - Long-Teng Shen; Miao Zhang; Zi-Yi Chen; Zhi-Cheng Wan (Fish & Shellfish Immunology, 2026)

VIS-NIR transmittance hyperspectral image reconstruction for litchi fruits - Teng Long; Ziran Xie; Yibin Luo; Min He; Dandan Liu; Xunjing Chen; Manyi Guan; Jing Zhao; Yubin Lan; Yongbing Long (Computers and Electronics in Agriculture, 2026)

Target-site and metabolic mechanisms confer broad resistance to PPO-inhibiting herbicides in Amaranthus retroflexus - Zhonghua Sun; Wenli Cao; Shen Wang; Long Du; Chang Liu; Dalong Li; Chunjie Li; Yi Feng; Xuelian Liu; Zitong Zhou; Xiaofeng Xu; Wenpeng Sun; et al. (Pesticide Biochemistry and Physiology, 2026)

Multidisciplinary modeling and dynamic Kriging assisted optimization for suborbital reusable launch vehicle - Teng Long; Haoda Li; Renhe Shi; Rong Chen; Baoshou Zhang; Nianhui Ye (Advances in Space Research, 2026)

Restormer_GAN: Rice UAV HSI reconstruction model and application in rice AGB estimation - Yibin Luo; Dandan Liu; Teng Long; Yubin Lan; Jing Zhao; Yongbing Long (Remote Sensing Applications: Society and Environment, 2026)

Research on detection methods of rice leaf area index based on multi-source UAV remote sensing data - Yihan Wang; Dandan Liu; Teng Long; Junjie Li; Hui Kang; Rongkun Chen; Yibin Luo; Yubin Lan; Zhenjiang Xu; Hong Liu; Haitao Xu; Yongbing Long (International Journal of Remote Sensing, 2026)

Dietary reuterin as a potential feed additive enhances growth performance, antioxidant capacity, and anti-inflammatory response in largemouth bass: Multi-omics insights into metabolic reprogramming - Jia-Le He; Han-Yin Xu; Yu-Long Sun; Tao Han; Jian-Kun Zhang; Qiang Chen; Ji-Teng Wang (Aquaculture, 2026)

Natural vivianite activates peroxymonosulphate for efficient ofloxacin degradation: Performance and mechanism - Teng Bao; Cheng long Li; Wei Wei; Mekdimu Mezemir Damtie; Zhijie Chen; Haijiao Xie; Bing-Jie Ni (Environmental Research, 2026)

Microneedles self-implanting Astragalus polysaccharides-hybridized composite hydrogel combined with minoxidil to enhance in situ anti-androgenetic alopecia - Jiaqi Li; Meng Long; Fanjun Xu; Zulalan Abudureyimu; Jing Li; Teng Guo; Nianping Feng; Yongtai Zhang (Drug Delivery and Translational Research, 2026)

Optical spin Hall effect driven by hybrid spin-orbit coupling in organic microcavities - Yongsheng Hu; Yuanjun Guan; Teng Long; Wei Xie; Hongxing Xu; Qing Liao; Zheng Sun; Jian Wu (Science Bulletin, 2026)

Human activities and horizontal gene transfer shape the resistome landscapes of non-human primates - Yue Sun; Mingyi Zhang; Yang Teng; Yueqi Yin; Jingcheng Ran; Haijun Su; Hongjia Li; Xiaolong Huang; Zexu Long; Xue Sun; Huijuan Pan; Xiaochen Wang; et al. (Journal of Hazardous Materials, 2026)

Assessment of CO2 storage potential in global marine sediments based on machine learning methods - Yang Zhang; Junjie Ji; Qiuming Cheng; Long Teng; Bingye Di (Global and Planetary Change, 2026)

Enzyme-detonated CRET nanocascade ignites endogenous chemiluminescence to empower self-sufficient photodynamic therapy and tumor-specific imaging - JiaXin Zhu; YanJun He; XiaoQian Wu; KangDi Teng; YiTeng Long; Yuan Zhang; Hui Sun; WenYuan Liu; Feng Feng; Wei Qu (Chemical Engineering Journal, 2026)

Bulk metagenomics and machine learning unravels nitrogen metabolism patterns in extreme-temperature marine environments - Zheng Guo; Yong-Guang Li; Xiao-Lin Liu; Zhao-Jie Teng; Qi-Long Qin; Qian-Qian Cha; Zhi-Bin Wang; Shou-Qing Ni (Bioresource Technology, 2026)

Platinum group elements and carbon cycle perturbation across the Permian-Triassic boundary in the Pingle Depression, South China: Evidence for volcanic flood basalt eruptions - Changjun Ji; Ahmed Mansour; Chaogang Fang; Long Teng; Yun Chen; Wang Qian (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Scalable SDS-templated CMCU@CaCl2 hydrogel with autonomous multisource hydration for atmospheric water harvesting and drought-resilient agriculture - Ayoub El Idrissi; QiRui Li; Teng Long; Yufan Liu; Yutao Xu; Youhui Chen; Banlian Ruan; Lingbin Lu (Chemical Engineering Journal, 2026)

Parallel Sympatric Divergence Driven by Disruptive Selection Acting on a Magic Temporal Isolation Trait in a Wild Annual Fish - Hao Yang; Teng‐Fei Xing; Yu‐Long Li; Jin‐Xian Liu (Molecular Ecology, 2026)
Sympatric speciation has long been of key interest among biologists, investigating how selection drives speciation in the absence of geographic isolation. However, the evolutionary trajectories and genetic architectures that underlie sympatric ecological divergence remain poorly understood. For the annual fish, Neosalanx brevirostris , from lakes in the Yangtze River basin, two sympatric ecotypes exhibit differences in reproductive season, with one breeding in spring and the other in autumn. Reproductive timing is considered a ‘magic trait’ in sympatric speciation, as it is both ecologically relevant and facilitates assortative mating. Using population genomic approaches, we investigated the genetic architecture of the adaptive sympatric divergence in reproductive season and the evolutionary forces driving this divergence by comparing two breeding ecotype pairs from two lakes and their ancestral anadromous population. Population genetic structure results provided strong evidence that sympatric ecological divergence has evolved independently and repeatedly in both lakes. Furthermore, we identified a set of genome‐wide candidate adaptive SNPs, which were present as standing genetic variations in ancestral population with high frequencies, and changes of allele frequency support that disruptive natural selection, induced by intensive resource competition, drove the reproductive season divergence. These adaptive SNPs were involved in various biological functions pertinent to reproductive timing, including photosensory, circadian entrainment, temperature sensing, and hormone signalling, highlighting the complex genetic architecture underlying reproductive seasonality. These findings provide valuable insights into the evolutionary trajectories and genetic architecture in the early stages of sympatric ecological divergence and speciation.

Coupling inertial effects and deterministic lateral displacement for high-purity microalgae separation in a microfluidic platform - Guibiao Qian; Long Wang; Zhihao Wu; Tianyi Wang; Shicheng Wan; Jianghao Zeng; Haonan Sun; Hong Yan; Liuyong Shi; Teng Zhou (Chemical Engineering Journal, 2025)

Lithium nitrate-stabilized electrolyte enabling wide-temperature and high-voltage lithium-ion batteries - Zhaojun Liu; Jiaxuan Feng; Rui Yang; Shen-ao Wang; Xiaochen Wu; Xiangyu Zhang; Sujuan Cheng; Ning Liu; Teng Long; Pengchao Si (Chemical Engineering Journal, 2025)

Actinobacteria mediate anaerobic methane oxidation in iron-rich environment - Shubing Li; Zhenzhen Peng; Shuguang Xie; Weiqi Chen; Ying Zhu; Wenwen Huang; Yi Tang; Mengchen Lu; Xunsen Chen; Teng Guo; Fangrong Wei; Jinshao Ye; et al. (Bioresource Technology, 2025)

Levonorgestrel-induced sex reversal in mandarin fish (Siniperca chuatsi): An effective protocol for all-female production and its aquaculture applications - Shiyan Liu; Jinmeng Teng; Suhan Peng; Shuang Liu; Jiaqi Lin; Long Chen; Ju Hu; Haoran Lin; Caiyun Sun; Shuisheng Li; Songlin Chen; Chong Han; et al. (Animal Reproduction Science, 2025)

Applying natural product repurposing strategy to identify baicalein as novel caseinolytic protease P inhibitor and its application in the treatment of rice bacterial diseases - Zhaoju Sun; Teng Yang; Zhouqing Long; Xichun Fu; Jiao Meng; Xiang Zhou; Cai-Guang Yang; Song Yang (Pesticide Biochemistry and Physiology, 2025)

Improved detection of soluble solid and anthocyanin in litchi fruits by normalized VNIR-SWIR transmittance hyperspectral imaging and SPF-SSF-GSF-NLF fusing method - Teng Long; Kangning Wei; Binshan Huang; Jun Du; Run Kuang; Haitao Xu; Jing Zhao; Yubin Lan; Yongbing Long (Food Chemistry, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Enhanced litchi fruit detection and segmentation method integrating hyperspectral reconstruction and YOLOv8 - Ziran Xie; Wentao Liu; Yuanhang Li; Jun Du; Teng Long; Haitao Xu; Yongbing Long; Jing Zhao (Computers and Electronics in Agriculture, 2025)

Reduced graphene oxide aerogel/polydimethylsiloxane biphasic composite with “button - like” interpenetrating dual - network structure for ultra - high and ultra - broad tunable sensitivity strain sensor - Jiyuan Han; Shihao Wang; Wei Zheng; Manman Wu; Xinyi Han; Teng Long; Chuanjian Zhou (Chemical Engineering Journal, 2025)

OC7 phase I: Toward practical sea-state-dependent modeling of hydrodynamic viscous drag and damping - Lu Wang; Amy Robertson; Jason Jonkman; Yingqian Liao; Petter Andreas Berthelsen; Serag-Eldin Abdelmoteleb; Peter Rohrer; Vishnu Ramachandran Nair Rajasree; Erin Bachynski-Polić; Constance Clement; Cédric Le Cunff; Prokopios Vlachogiannis; et al. (Ocean Engineering, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Mineralogy and elemental geochemistry of Pennsylvanian high-sulfur coals in the Huanghebei Coalfield, Shandong, Northern China: Implications for the enrichment and controlling factors of U - Bofei Zhang; Wenfeng Wang; Qingfeng Lu; Wenlong Wang; Xiaozhen Teng; Long Chen (International Journal of Coal Geology, 2025)

Context-dependent anaerobic oxidation of methane: Insight for methane emission mitigation - Wenwen Huang; Yi Tang; Mengchen Lu; Zhenzhen Peng; Shubing Li; Xunsen Chen; Fangrong Wei; Teng Guo; JinShao Ye; Yan Long (Journal of Environmental Management, 2025)

Influence of sedimentary environment on rock physical properties of saline lacustrine shale: A case study from the upper member of the Lower Ganchaigou Formation - Hui Xia; Ji-xin Deng; Lian-teng Song; Jian-gong Wang; Ping Zhang; Zhong-hua Liu; Hong-liang Wu; Jia-qing Wang; Yan Long-long (Applied Geophysics, 2025)

Lanthanum substitution enhances the intrinsic phosphate-adsorption capacity of hydrated ferric oxide via increasing Fe electron density - Xiaohui Wang; Xue Li; Yifei Teng; Junyu Lang; Lizhi Zhang; Mingce Long (Chemical Engineering Journal, 2025)

Crown-rich alginate aerogel with ultra-high adsorption capacity for lithium-ion via a Möbius strip-inspired “Opening and Re-Ring” strategy - Yutao Xu; Youhui Chen; Ayoub EL Idrissi; Banlian Ruan; Longfei Ma; Teng Long; Yufan Liu; Hong Jiang; Lingbin Lu (Chemical Engineering Journal, 2025)

Pollution risk assessment and source apportionment of potentially toxic elements in agricultural soils using the APCS-MLR model: a case study near a non-ferrous metal smelting slag site in Gejiu, Yunnan - Chao-liang Peng; Zhe Wang; Ying Luo; Jia-Qian Zhang; Zhen-Long Zhang; Yi-ming Chen; Kai Ye; Wen-xue Lin; Jing-yan Zhang; Teng-jiao Xie (Environmental Monitoring and Assessment, 2025)

Synergistic Regulation of Color Transformation by Nutrient Elements, Osmotic Regulators, and Antioxidant Enzymes in Erythrophleum fordii - Zi-Long Ouyang; Xiang-Lu Jia; Tian-dao Bai; Lin-juan Huang; Xuan Jiang; Wei-Chao Teng (Journal of Plant Growth Regulation, 2025)

Evaluation of thermal death kinetic models of Salmonella Typhimurium ATCC 14028 and application for radio frequency pasteurization of shell eggs - Teng Cheng; Jiale Zhao; Long Chen; Jing Lv; Jianhang Hu; Wenhao Sun; Feixue Yang; Huanyun Ding; Qisen Xiang; Yanhong Bai (Innovative Food Science & Emerging Technologies, 2025)

Green revolution gene drives adaptation of Arabidopsis to the extremely high altitude - Xing-Hui Hou; Yong-Chao Xu; Tianshu Sun; Yan-Bo Gong; Xin-Tong Li; Guang-Teng Jin; Yu-Tao Bian; Yi-Ni Liu; Juan Jiang; Xiao-Min Niu; Hongya Gu; Ya-Long Guo (Science China Life Sciences, 2025)

Microwave replacing traditional concentrating process to promote the synthesis of mumefural in Prunus mume extract - Teng Long Miao; Shan Qin; Xiao Hong Chen; Long Yun Chen; Yan Qing Han; Yan Li Yuan; Xin Rui; Wei Li; Qiu Qin Zhang (Food Research International, 2025)

The impact of organic matter and iron/calcium coupling on phosphorus retention in the hyporheic zone of the Danjiangkou area tributary: Evidence from bonding recognition - Yu Chen; Teng Ma; Liuzhu Chen; Jiabao Sun; Keyu Long; Gongyu Zhou; Weidong Sun (Science of The Total Environment, 2024)

Detecting bioactive compound contents in Dancong tea using VNIR-SWIR hyperspectral imaging and KRR model with a refined feature wavelength method - Teng Long; Xinyu Tang; Changjiang Liang; Binfang Wu; Binshan Huang; Yubin Lan; Haitao Xu; Shaoqun Liu; Yongbing Long (Food Chemistry, 2024)

Seismic anisotropy of granitic rocks from a fracture stimulation well at Utah FORGE using ultrasonic measurements - Mayra D.L. Carrasquilla; Min Sun; Teng Long; Virginia Sisson; Thomas Lapen; Clay Jones; Joseph Moore; Lianjie Huang; Yingcai Zheng (Geothermics, 2024)

Arginine alleviates LPS-induced leukocytes inflammation and apoptosis via adjusted NODs signaling - Yuan-Xin Qian; Feng-Feng Zhou; Qiang Chen; Fen Dong; Han-Ying Xu; Yu-Long Sun; Ji-Teng Wang; Tao Han (Fish & Shellfish Immunology, 2024)

Dual-continuous microneedle patch integrating transdermal delivery of pH-sensitive licorzinc MOFs and Zn2+ hydrogel sensors for treating alopecia areata - Hang Ruan; Yuwen Zhong; Huining Ding; Zehui He; Jiaqi Li; Meng Long; Zhi Wang; Qing Xia; Teng Guo; Chunyun Zhu; Tao Yang; Nianping Feng; et al. (Chemical Engineering Journal, 2024)

Energy management system for hybrid ship: Status and perspectives - Xiaodong Guo; Xiao Lang; Yupeng Yuan; Liang Tong; Boyang Shen; Teng Long; Wengang Mao (Ocean Engineering, 2024)

Semi-Conv-DETR: A railway ballast bed defect detection model integrating convolutional augmentation and semi-supervised DETR - Jing Teng; Xujie Long; Qi Yang; Guoqing Jing; Huan Liu (Transportation Geotechnics, 2024)

Meta-omics analysis reveals the marine arsenic cycle driven by bacteria - Zhao-Jie Teng; Jian Li; Peng Wang; Chun-Yang Li; Ming Peng; Qi-Long Qin; Xiu-Lan Chen; Yin Chen; Hui-Hui Fu; Ning Wang; Yu-Zhong Zhang (Journal of Hazardous Materials, 2024)

Discovery of Late Carboniferous high-grade carbonate-hosted manganese mineralization in the Maerkansu area of the Western Kunlun Orogen, Northwest China - Yongbao Gao; Leon Bagas; Yuegao Liu; Wenyuan Li; Keiko Hattori; Dominic Papineau; Delong Jing; Denghui Chen; Jiaxin Teng; Yongkang He; Min Zhao; Long Zhang; et al. (Gondwana Research, 2024)

Cytoplasmic tail of transmembrane dscam controls antibacterial responses by regulating cell proliferation-related genes in hemocytes of Chinese mitten crab (Eriocheir sinensis) - Hong-hao Xia; Le-mei Zhu; Long-teng Shen; Zhi-cheng Wan (Fish & Shellfish Immunology, 2024)

Transcriptome-wide analysis of a superior xylan degrading isolate Penicillium oxalicum 5–18 revealed active lignocellulosic degrading genes - Shuang Hu; Pei Han; Bao-Teng Wang; Long Jin; Hong-Hua Ruan; Feng-Jie Jin (Archives of Microbiology, 2024)

Chemical constitutents and chemotaxonomic research of the deep-sea-derived fungus Talaromyces minioluteus W19 - Kai Zhang; Yuan Wang; Teng Long; Ya-Ping Xie; Zheng-Biao Zou; Yong Zhang; You Li; Ming-Min Xie; Guang-Ming Liu; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Iron-containing nanominerals for sustainable phosphate management: A comprehensive review and future perspectives - Teng Bao; Mekdimu Mezemir Damtie; Chu Yan Wang; Cheng Long Li; Zhijie Chen; Kuk CHO; Wei Wei; Peng Yuan; Ray L. Frost; Bing-Jie Ni (Science of The Total Environment, 2024)

Investigation of hydrogen-propane hydrate formation mechanism and optimal pressure range via hydrate-based hydrogen storage - Pengfei Wang; Hao Long; Ying Teng; Yinglong Li; Yun Li; Jianbo Zhu; Heping Xie; Songbai Han; Yusheng Zhao; Jinlong Zhu (Fuel, 2024)

Metabolomics-based study of chemical compositions in cellulase additives derived from a tobacco-origin Bacillus subtilis and their impact on tobacco sensory attributes - Xiaofeng Chen; Teng Long; Shixin Huang; Yiqiang Chen; Hongliang Lu; Zhenkun Jiang; Cheng Cheng; Jingjing Li; Shanyi Chen; Wei He; Xu Tang; Jianqiang Fan (Archives of Microbiology, 2024)

Characterization of potassium-solubilizing fungi, Mortierella spp., isolated from a poplar plantation rhizosphere soil - Rui Zhu; Long Jin; Yue Sang; Shuang Hu; Bao-Teng Wang; Feng-Jie Jin (Archives of Microbiology, 2024)

Insight into the high-temperature oxidation kinetics of acetylene: A first-principles molecular dynamics study - Teng Zhang; Liefeng Shou; Kun Yang; Yao Long; Lang Chen; Hongliang Wang; Jun Chen (Journal of Hazardous Materials, 2024)

Effects of dimethyl ether blending on H2-fueled combustion characteristics and thermal improvement in fuel-lean condition - Jia Wei; Hao Wang; Qingguo Peng; Xinghua Tian; Feng Yan; Long Zhang; Peng Teng; Shuai Fu (Fuel, 2024)

Sedimentary record of microplastics in coastal wetland, eastern China - Yujie Zhou; Shenglu Zhou; Sophia Shuang Chen; Yan Li; Long Chen; Qi Zhang; Bo Su; Teng Wang (Water Research, 2024)

Complete genome sequence analysis of Bacillus velezensis A5, a promising biocontrol agent from the Pacific Ocean - Shunhua Ji; Yin Tian; Guangxin Xu; Yiqiang Chen; Jingjing Li; Teng Long; Wei He; Jianqiang Fan; Xixiang Tang (Marine Genomics, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Integrated analysis of transcriptome and metabolome reveals the regulatory mechanism of largemouth bass (Micropterus salmoides) in response to Nocardia seriolae infection - Fen Dong; Yu-Long Sun; Yuan-Xin Qian; Qiang Chen; Jia-Le He; Ji-Teng Wang; Tao Han; Xiu-Mei Zhang; Yu-Ting Deng (Fish & Shellfish Immunology, 2024)

Petrogenesis and tectonic implications of the Silurian adakitic granitoids in the eastern segment of the Qilian Orogenic Belt, Northwest China - Jiao-Long Zhao; Xiao-Jun Huang; Pei-Qing Hu; Zhen-Xi Yang; Ying Fan; Er-Teng Wang; Fu-Bo Yang; Jing-Yu Zhang (Acta Geochimica, 2024)

High performance polydimethylsiloxane elastomer for triboelectric nanogenerators in extreme environment - Wencan Ma; Teng Long; Haomin Wu; Jia-Han Zhang; Yan Lyu; Mengke Zhao; Jia Li; Qiuhong Zhang; Chuanjian Zhou; Chen Zhang; Guigan Fang (Chemical Engineering Journal, 2024)

Trends in the occurrence and accumulation of microplastics in urban soil of Nanjing and their policy implications - Yujie Zhou; Teng Wang; Mengmeng Zou; Qiqi Yin; Zhenyi Jia; Bo Su; Qi Zhang; Long Chen; Shenglu Zhou (Science of The Total Environment, 2023)

Transport of pollutants in groundwater of domestic waste landfills in karst regions and its engineering control technologies - Bo Li; Teng Li; Pan Wu; Lei Yang; Jie Long; Pu Liu; Tao Li (Journal of Environmental Management, 2023)

By-product of hydrothermal liquefaction: Characterization of biochar and its application in metal-free electrochemical advanced oxidation process of hydrogen peroxide to provide hydroxyl radicals - Hongbiao Du; Zeqing Long; Guang Xian; Shuai Lu; Sheng Zhang; Sifan Liu; Youchao Teng; Jinglai Zhang; Huansheng Wang (Journal of Environmental Chemical Engineering, 2023)

Modified Kozeny-Carman equation for estimating hydraulic conductivity in nanoscale pores of clayey soils with active surfaces - Yu Zhong; Annan Zhou; Jiapei Du; Jidong Teng; Shui-long Shen (Journal of Hydrology, 2023)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

A Generalized Unified Strength Theory for Rocks - Hang-Zhou Li; Jian-Teng Xu; Zhi-Long Zhang; Li Song (Rock Mechanics and Rock Engineering, 2023)

Locating the Scope and Depth of Coal Fires Based on Magnetic and Electrical Data - Zhenlu Shao; Guofu Zhang; Tao Zhou; Jun Wei; Fei Cao; Yong Zhang; Hongsheng Li; Huahai Sun; Shangkun Qing; Teng Chen; Long Chen; Hongwen Shao; et al. (Pure and Applied Geophysics, 2023)

Does digitalization enhance fossil fuels resources efficiency? - Nan Liu; Long Teng; Wenjuan Tian; Ying Li (Resources Policy, 2023)

The mechanism responsible for the geochemical diversity of the Putuoshan volcanic-plutonic complex and its implications for the late Mesozoic crustal evolution of the Cathaysia Block, Southeast China - Jiao-Long Zhao; Liang Liu; Hang Xu; Er-Teng Wang (Lithos, 2023)

Evaluating the ecological vulnerability of Chongqing using deep learning - Jun-Yi Wu; Hong Liu; Tong Li; Yuan Ou-Yang; Jing-Hua Zhang; Teng-Jiao Zhang; Yong Huang; Wen-Long Gao; Lu Shao (Environmental Science and Pollution Research, 2023)

Rayleigh surface wave inversion based on an improved Archimedes optimization algorithm - Zhen-An Yao; Ren Wang; Fu Yu; Long-Feng Chen; Hong-Xing Li; Xiang-Teng Wang; Pan Wang (Applied Geophysics, 2023)

Ambient nitrogen dioxide and cardiovascular diseases in rural regions: a time-series analyses using data from the new rural cooperative medical scheme in Fuyang, East China - Teng-Fei Dong; Zhen-Qiu Zha; Liang Sun; Ling-Li Liu; Xing-Yang Li; Yuan Wang; Xiang-Long Meng; Huai-Biao Li; Hong-Li Wang; Huan-Huan Nie; Lin-Sheng Yang (Environmental Science and Pollution Research, 2023)

Calcium ion removal at different sodium chloride concentrations by free and immobilized halophilic bacteria - Huaxiao Yan; Jiahao Cao; Minhan Teng; Long Meng; Lanmei Zhao; Xiangqun Chi; Zuozhen Han; Maurice E. Tucker; Hui Zhao (Water Research, 2023)

A detection approach for late-autumn shoots of litchi based on unmanned aerial vehicle (UAV) remote sensing - Juntao Liang; Xin Chen; Changjiang Liang; Teng Long; Xinyu Tang; Zhenmiao Shi; Ming Zhou; Jing Zhao; Yubin Lan; Yongbing Long (Computers and Electronics in Agriculture, 2023)

Identification of tropical cyclone centre based on satellite images via deep learning techniques - Teng Long; Jiyang Fu; Biao Tong; Pakwai Chan; Yuncheng He (International Journal of Climatology, 2022)
A tropical cyclone (TC) is a highly destructive natural disaster. Accurate identification of key parameters of TCs is prerequisite for most TC‐related research and practices. The centre position is one of TC's basic parameters. However, comparison of TC best track data released by different meteorological institutes usually indicates a noticeable discrepancy for this parameter among varied data sources. In this study, efforts are made towards identifying the centre location of TCs via deep learning techniques, based on TC satellite cloud images (SCIs). Six deep learning models are analysed and compared. YOLOv4 model achieved a confidence of 99.84%, which is better than other models. In addition, we further explore the factors affecting the positioning accuracy of the YOLOv4 model and its application to the location identification of multiple TCs and the tracking of individual TCs. Results demonstrate that the YOLOv4 model has a probability exceeding 99% for identifying multiple TC locations and also performs well for single TC tracking.

Orientin downregulating oxidative stress-mediated endoplasmic reticulum stress and mitochondrial dysfunction through AMPK/SIRT1 pathway in rat nucleus pulposus cells in vitro and attenuated intervertebral disc degeneration in vivo - Zhao Zhang; Jingtao Wu; Cheng Teng; Jinquan Wang; Jiapei Yu; Chen Jin; Libo Wang; Long Wu; Zhen Lin; Ziping Yu; Zhongke Lin (Apoptosis, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Analysis of studies on environmental measurements using diffusive gradients in thin-films (DGT) from 1994 to 2020 - Tian-Jiao Wei; Dong-Xing Guan; Xi-Yuan Li; Yi-Long Hao; H. Henry Teng; Ji-Feng Yang; Yao-Yang Xu; Gang Li (Journal of Soils and Sediments, 2022)

Dietary Selenium Deficiency and Excess Accelerate Ubiquitin-Mediated Protein Degradation in the Muscle of Rainbow Trout (Oncorhynchus mykiss) via Akt/FoxO3a and NF-κB Signaling Pathways - Feng Zhang; Zhenlei Teng; Li Wang; Long Wang; Taotao Huang; Xuezhen Zhang (Biological Trace Element Research, 2022)

Lignans from Euphorbia hirta L. - Ling Zhang; Xiao-Ling Wang; Bin Wang; Long-Teng Zhang; Hui-Min Gao; Tao Shen; Hong-Xiang Lou; Dong-Mei Ren; Xiao-Ning Wang (Natural Product Research, 2022)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Diversity of the type I-U CRISPR-Cas system in Bifidobacterium - Liuyang Ou; Jinzhao Long; Yanli Teng; Haiyan Yang; Yuanlin Xi; Guangcai Duan; Shuaiyin Chen (Archives of Microbiology, 2021)

Fast overlapped subaperture algorithm for high-squint spotlight SAR imaging - Yan Wang; Zegang Ding; Minkun Liu; Tao Zeng; Teng Long (International Journal of Remote Sensing, 2020)

Effect of three Napier grass varieties on phytoextraction of Cd- and Zn-contaminated cultivated soil under mowing and their safe utilization - Wen-Jun Yang; Jiao-Feng Gu; Hang Zhou; Fang Huang; Teng-Yue Yuan; Jing-Yi Zhang; Shi-Long Wang; Zhi-Guang Sun; Hong-Wei Yi; Bo-Han Liao (Environmental Science and Pollution Research, 2020)

Organic ligands unexpectedly increase the toxicity of chromium(III) for luminescent bacteria - Weijie Zhou; Wenjun Long; Teng Xu; Liangqiong Peng; Wenhua Zhang (Environmental Chemistry Letters, 2019)

Recombinant rabies virus expressing interleukin-6 enhances the immune response in mouse brain - Jun Luo; Boyue Zhang; Yuting Wu; Qin Tian; Meijun Mo; Teng Long; Mingzhu Mei; Ruqi Fan; Ziyu Lyu; He Jiang; Fan Wu; Yingyi Lin; et al. (Archives of Virology, 2018)

Characterization of dominant giant rod-shaped magnetotactic bacteria from a low tide zone of the China Sea - Zhaojie Teng; Wenyan Zhang; Yiran Chen; Hongmiao Pan; Tian Xiao; Long-Fei Wu (Journal of Oceanology and Limnology, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Antioxidants Attenuate Acute and Chronic Itch: Peripheral and Central Mechanisms of Oxidative Stress in Pruritus - Feng-Ming Zhou; Ruo-Xiao Cheng; Shuai Wang; Ya Huang; Yong-Jing Gao; Yan Zhou; Teng-Teng Liu; Xue-Long Wang; Li-Hua Chen; Tong Liu (Neuroscience Bulletin, 2017)

PPARδ agonist GW0742 ameliorates Aβ1–42-induced hippocampal neurotoxicity in mice - Yun-Qi An; Chun Teng Zhang; Yong Du; Ming Zhang; Su Su Tang; Mei Hu; Yan Long; Hong Bing Sun; Hao Hong (Metabolic Brain Disease, 2016)

Low-Dose Endothelial Monocyte-Activating Polypeptide-II Increases Blood–Tumor Barrier Permeability by Activating the RhoA/ROCK/PI3K Signaling Pathway - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Jing Liu; Hao Teng; Zhuo Xi; Yi-long Yao (Journal of Molecular Neuroscience, 2016)

Fluorescence spectroscopy reveals accompanying occurrence of ammonium with fulvic acid-like organic matter in a fluvio-lacustrine aquifer of Jianhan Plain - Shuangbing Huang; Yanxin Wang; Teng Ma; Yanyan Wang; Long Zhao (Environmental Science and Pollution Research, 2016)

Low-Dose Endothelial Monocyte-Activating Polypeptide-II Induces Blood–Tumor Barrier Opening Via the cAMP/PKA/Rac1 Pathway - Zhen Li; Xiao-bai Liu; Yun-hui Liu; Yi-xue Xue; Jing Liu; Hao Teng; Zhuo Xi; Yi-long Yao (Journal of Molecular Neuroscience, 2016)

Cancer incidence in the vicinity of nuclear power plants in Taiwan: a population-based study - Shiow-Ing Wang; Chih-Liang Yaung; Long-Teng Lee; Shang-Jyh Chiou (Environmental Science and Pollution Research, 2016)

ERK5 signalling pathway is essential for fluid shear stress-induced COX-2 gene expression in MC3T3-E1 osteoblast - Jin Jiang; Liang-gong Zhao; Yuan-jun Teng; Shao-long Chen; Li-ping An; Jing-ling Ma; Jing Wang; Ya-yi Xia (Molecular and Cellular Biochemistry, 2015)

Phthalate esters contamination in soils and vegetables of plastic film greenhouses of suburb Nanjing, China and the potential human health risk - Ting Ting Ma; Long Hua Wu; Like Chen; Hai Bo Zhang; Ying Teng; Yong Ming Luo (Environmental Science and Pollution Research, 2015)

Expression profiles of miRNAs in Gossypium raimondii - Jun Ma; Teng-long Guo; Qing-lian Wang; Kun-bo Wang; Run-run Sun; Bao-hong Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

Identification and characterization of a novel phage display-derived peptide with affinity for human brain metastatic breast cancer - Bo Fu; Ying Zhang; Wei Long; Aifeng Zhang; Yafen Zhang; Yanli An; Fengqin Miao; Fang Nie; Mingli Li; Youji He; Jianqiong Zhang; Gaojun Teng (Biotechnology Letters, 2014)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Yeast-Incorporated Gallium Attenuates Glucocorticoid-Induced Bone Loss in Rats by Inhibition of Bone Resorption - Zhaozhou Ren; Liqing Yang; Feng Xue; Qingjie Meng; Kejia Wang; Xian Wu; Chao Ji; Teng Jiang; Da Liu; Long Zhou; Jing Zhang; Qin Fu (Biological Trace Element Research, 2013)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Improvement of arachidonic acid and eicosapentaenoic acid production by increasing the copy number of the genes encoding fatty acid desaturase and elongase into Pichia pastoris - Yun-Tao Li; Mao-Teng Li; Chu-Hua Fu; Peng-Peng Zhou; Jian-Min Liu; Long-Jiang Yu (Biotechnology Letters, 2009)

ACL reconstruction with BPTB autograft and irradiated fresh frozen allograft - Kang Sun; Shao-qi Tian; Ji-hua Zhang; Chang-suo Xia; Cai-long Zhang; Teng-bo Yu (Journal of Zhejiang University-SCIENCE B, 2009)

Microbial production of 1,3-propanediol by Klebsiella pneumoniae using crude glycerol from biodiesel preparations - Ying Mu; Hu Teng; Dai-Jia Zhang; Wei Wang; Zhi-Long Xiu (Biotechnology Letters, 2006)

Cloning and tissue distribution of the human B3GALT7 gene, a member of the β1,3-Glycosyltransferase family - Chaoqun Huang; Jialiang Zhou; Shiliang Wu; Yuxi Shan; Shaolei Teng; Long Yu (Glycoconjugate Journal, 2004)

Inheritance and segregation of exogenous genes in transgenic cotton - Bao-Hong Zhang; Teng-Long Guo; Qing-Lian Wang (Journal of Genetics, 2000)